2022
DOI: 10.1186/s10020-022-00540-2
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between autophagy and the epithelial-mesenchymal transition mediated by NICD/ULK1 is involved in the formation of diabetic cataracts

Abstract: Background Cataracts are the leading cause of blindness and a common ocular complication of diabetes. The epithelial-mesenchymal transition (EMT) of lens epithelial cells (LECs) and altered autophagic activity occur during the development of diabetic cataracts. The disturbed interaction of autophagy with EMT in LECs stimulated by high glucose levels may participate in cataract formation. Methods A rat diabetic cataract model induced by streptozotoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…As a "medicine food homology" plant, many bioactive ingredients have been confirmed in PS, including polysaccharides, steroidal saponins, amino acids, flavonoids, anthraquinones, and alkaloids (Zeng et al, 2020). Modern pharmacological studies have demonstrated that PS decreases blood glucose (Ma et al, 2022) and blood pressure (Su et al, 2022), prevents atherosclerosis (Zhu et al, 2015), enhances immunity (Sun et al, 2022), and has anti-fatigue (Shen et al, 2021), anti-tumor (Li et al, 2022), and anti-aging effects (Chen et al, 2020). According to the previous study, the polysaccharide of PS could improve D-gal-induced aging rats' state by up-regulating the expression of Klotho, and down-regulating the expression of FOXO3a in the mRNA and protein levels (Zheng, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As a "medicine food homology" plant, many bioactive ingredients have been confirmed in PS, including polysaccharides, steroidal saponins, amino acids, flavonoids, anthraquinones, and alkaloids (Zeng et al, 2020). Modern pharmacological studies have demonstrated that PS decreases blood glucose (Ma et al, 2022) and blood pressure (Su et al, 2022), prevents atherosclerosis (Zhu et al, 2015), enhances immunity (Sun et al, 2022), and has anti-fatigue (Shen et al, 2021), anti-tumor (Li et al, 2022), and anti-aging effects (Chen et al, 2020). According to the previous study, the polysaccharide of PS could improve D-gal-induced aging rats' state by up-regulating the expression of Klotho, and down-regulating the expression of FOXO3a in the mRNA and protein levels (Zheng, 2020).…”
Section: Introductionmentioning
confidence: 99%